A triple‐probe FISH screening strategy for risk‐stratified therapy of acute lymphoblastic leukaemia in low‐resource settings. Issue 12 (31st August 2018) - Parihar, Mayur; Singh, Manish K.; Islam, Rubina; Saha, Debparna; Mishra, Deepak Kumar; Saha, Vaskar; Krishnan, Shekhar
Abstract: Karyotyping along with a 3‐probe fluorescence in situ hybridization (FISH) strategy was used to risk stratify therapy in 303 children with B‐cell precursor acute lymphoblastic leukaemia. Of the 166 patients risk stratified, karyotype identified 91 (55%). FISH identified all karyotypes accurately, with the exception of hypodiploidy, and risk stratified an additional 75 patients. The frequency of ETV6‐RUNX1 is lower and high hyperdiploidy, higher than reported in the west. An adapted 3‐probe FISH strategy identified two patients with ETV6‐ABL1 fusion who received imatinib. In limited‐resource settings, a 3‐probe FISH approach provides a practical approach for risk‐stratified therapy in childhood ALL.